CORRELATION BETWEEN METACOGNITIVE FACTORS AND ACADEMIC ACHIEVEMENT IN MATHEMATICS AMONG SECONDARY SCHOOLS STUDENTS IN ORON LOCAL GOVERNMENT AREA OF AKWA IBOM STATE, NIGERIA - EKPENYONG EFFIONG IBOK; EDET OKON UNOH; FRANCISCA FRANCIS ASUQUO (International Studies Journal)
This study adopted correlational   design to examine correlation between metacognitive factors    and academic achievement in mathematics among secondary school students   in Oron Local Government, Akwa Ibom State, Nigeria. Two research questions were posed and two hypotheses formulated to guide the study.  Proportionate   sampling    technique was   used to select   a sample of 300 SS2 students    for the study.   Two     instruments titled   questionnaire   Metacognitive Factors (MCF)” and Mathematics Achievement Test (MAT) were   developed by the researcher and validated by experts and used for data collection. The average reliability of the instrument was determined and the coefficient using Alpha Cronbach Method    and   Kuder-Richardson formula (21) was found to be 0.84 and 0.87 for meta cognitive factors   and   Mathematics achievement   respectively. The hypotheses were tested using Pearson Product Moment Correlation    for hypotheses   for   two    hypotheses. All   hypotheses   were   tested at -05 level of significance. Findings indicated that both    self –assessment   and self-resilience    were significant relate to academic achievement in mathematics. It was concluded that    achievement    of students in mathematics   depend on their meta cognitive   factors   in terms of self-assessment and self-resilience.  It was recommended amongst others   that educators should implement strategies that build students' confidence in their mathematical abilities which should include providing self-assessment, self-resilience, setting achievable goals, and celebrating small successes.